Development of a laboratory model to demonstrate load management in a smart grid - Azim, Syeda Mayesha; Shahidi, Salwa; Tarannum, Rehenuma; Tahora, Sharaban (BRAC University, 2014)
This thesis report submitted in partial fulfillment of the requirement for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2014.